2016
DOI: 10.1152/ajpheart.00235.2016
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin-binding protein Smyd1 restricts adult mammalian heart growth

Abstract: All terminally differentiated organs face two challenges, maintaining their cellular identity and restricting organ size. The molecular mechanisms responsible for these decisions are of critical importance to organismal development, and perturbations in their normal balance can lead to disease. A hallmark of heart failure, a condition affecting millions of people worldwide, is hypertrophic growth of cardiomyocytes. The various forms of heart failure in human and animal models share conserved transcriptome remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 53 publications
1
64
0
Order By: Relevance
“…Recently, we found that Smyd1 expression is differentially regulated during pressure overload cardiac hypertrophy and failure in mice (4), consistent with its expression in the failing human heart (5). In addition, we showed that loss of Smyd1 in the adult mouse heart was sufficient to induce hypertrophic growth, which progressed to fulminant heart failure (4). Analysis of the cardiac transcriptome in these Smyd1-KO mice revealed dysregulation of pathways responsible for development, muscle growth, and metabolism (4).…”
supporting
confidence: 61%
See 3 more Smart Citations
“…Recently, we found that Smyd1 expression is differentially regulated during pressure overload cardiac hypertrophy and failure in mice (4), consistent with its expression in the failing human heart (5). In addition, we showed that loss of Smyd1 in the adult mouse heart was sufficient to induce hypertrophic growth, which progressed to fulminant heart failure (4). Analysis of the cardiac transcriptome in these Smyd1-KO mice revealed dysregulation of pathways responsible for development, muscle growth, and metabolism (4).…”
supporting
confidence: 61%
“…Our initial analysis of inducible, cardiac-specific Smyd1-KO revealed down-regulation of numerous genes involved in metabolism. However, these transcriptomic changes were accompanied by significant structural remodeling of the heart and severe heart failure (4). Thus, Significance Smyd1 is a muscle-specific histone methyltransferase, and its role in the regulation of growth and differentiation in skeletal and cardiac muscle is well established.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, ROS decreased levels of the H3K4 methyltransferase SET and MYND domain‐containing protein 1 (SMYD1) in a model of cardiac pressure overload, and thioredoxin restored SMYD1 levels (Figure ) and cardiac function indicating that HMTs might differ in their ROS sensitivity depending on the pathophysiological context although histone lysine methylation was not determined in this study (Liu et al , ). As activation of SMYD1 has been considered to prevent cardiac hypertrophy and even heart failure, such a ROS‐related pathway might have important implications for further cardiovascular therapies (Franklin et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%